Diversidade genética em xiquexique (Pilosocereus gounellei (Web.) Byl. & Rowl.) utilizando marcadores SSR e AFLP - Monteiro, Eliane Rodrigues (2013)
Pilosocereus gounellei is common in Semiarid region, which is under the dominion geoecológico Caatinga biome, where it is popularly known as xiquexique. The objective of the present study was to evaluate the genetic diversity and similarity at the DNA level of P. gounellei among samples from the Piauí, Bahia e Rio Grande do Norte States. For the characterization of microsatellite markers were assessed 33 pairs of microsatellite primers developed for different species of cactaceae. Five pairs of microsatellite primers developed for Astrophytum asterias, Polaskia chichipe and Echinocactus grusonii, were selected resulting a 24.24% transferability of these primers for P. gounellei. The polymorphism to average of samples of P. gounellei was 73.05%, the evaluated loci showed 18 alleles, with an average of 3.6 alleles per locus. Seven primer pairs used amplified 703 AFLP markers, of which 700 (99.21%) were polymorphic. The percentage of polymorphic fragments ranged from 95.3% for the primer combination E-AAG/M-CTT to 100% for E-ACC/M-CAT, E-ACC/M-CAA, EAGC/M-CAG, E-ACT/M-CTA, E-ACT/M-CTA e E-AGG/M-CTG. The largest number of informative markers (126) was detected using the primer combination E-AAC/M-CTA, while the E-AAG/M-CTT combination revealed the lowest number of polymorphic fragments (48). Nei's gene diversity was 0.3064. The low value of GST (0.1353) and high amount of gene flow (3.1968) indicate that the genetic differentiation within populations of the three states is higher than among the populations of the three states. In the dendrogram based on the Jaccard similarity coefficient, the samples were divided into two groups. Our results demonstrated that AFLP markers were efficient to genetic characterization in the samples P. gounellei. SSR and AFLP techniques can be applied to estimate the genetic diversity and genetic structure this species.